Expression of chIL-6 gene encoding chicken interleukin-6 in E. coli BL21(DE3) - Thu Huyen, Vu Thi; Cuong, Pham Viet; Kim Dung, Tran Thi; Kim Cuc, Nguyen Thi (Academia Journal of Biology, 2012)
Interleukin-6 (IL-6) is a multifunctional cytokine having a wide range of activity and has an impact on almost immune system cells such as B cells , T cells, hepatocytes, haematopoietic progenitor cells and cells of the central nervous system. IL-6 is produced by many different cell types and acts as pro- and antiinflammation cytokine. For effective expression in prokaryotic system, the cloned Vietnames chIL-6 gene was optimized using Optimum Gene Codon Optimization Analysis and the CAI was improved up to 0.89. The expression vector pGS-21a-chIL-6 containing optimized chIL-6 gene was successfully constructed. By induction with IPTG, recombinant chIL-6 protein was expressed in BL21. The ELISA resuls and Polyacrylamid gel showed that expressed protein has molecular weight about 27 kDa, corresponding to theoretical calculation and mainly in inclusion bodies state.